Real-time imaging of RGC death with a cell-impermeable nucleic acid dyeing compound after optic nerve crush in a murine model. (May 2016) - Tsuda, Satoru; Tanaka, Yuji; Kunikata, Hiroshi; Yokoyama, Yu; Yasuda, Masayuki; Ito, Azusa; Nakazawa, Toru
Abstract: The retinal ganglion cells (RGCs) are the main source of therapeutic targets for neuroprotective glaucoma treatment, and evaluating RGCs is key for effective glaucoma care. Thus, we developed a minimally invasive, quick, real-time method to evaluate RGC death in mice. In this article we describe the details of our method, report new results obtained from C57BL/6J mice, and report that our method was usable in wild type (WT) and knockout (KO) mice lacking an RGC-death-suppressing gene. It used a non-invasive confocal scanning laser ophthalmoscope (cSLO) and a low molecular weight, photo-switching, cell-impermeant, fluorescent nucleic acid dyeing compound, SYTOX orange (SO). The RGCs were retrogradely labeled with Fluorogold (FG), the optic nerve was crushed (ONC), and SO was injected into the vitreous. After ten minutes, RGC death was visualized with cSLO in vivo . The retinas were then extracted and flat mounted for histological observation. SO-labeled RGCs were counted in vivo and FG-labeled RGCs were counted in retinal flat mounts. The time course of RGC death was examined in Calpastatin KO mice and wild type (WT) mice. Our in vivo imaging method revealed that SO-positive dead RGCs were mainly present from 4 to 6 days after ONC, and the peak of RGC death was after 5 days. Moreover, the number of SO-positive dead RGCs after 5 days differed significantly in the Calpastatin KO mice and the WT mice. Counting FG-labeled RGCs in isolated retinas confirmed these results. Thus, real-time imaging with SO was able to quickly quantify ONC-induced RGC death. This technique may aid research into RGC death and the development of new neuroprotective therapies for glaucoma. Highlights: Visualizing dead RGCs in vivo with a photo-switching nucleonic acid dyeing compound. Real time imaging could detect RGC death in mice quickly and quantitatively. Our method showed that RGC death is highest 5 days after axonal injury. Our method showed that RGC death is enhanced in mice lacking the Calpastatin gene.